IMPLEMENTASI METODE MIND MAPPING BERBASIS SOFTWARE GITMIND PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH KEJURUAN NEGERI 8 SURABAYA - Asrori Asrori; Ifni Hirnayatul Perada Lema; Rusman Rusman (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2023)
This research is based on a phenomenon at SMKN 8 Surabaya which shows a variety of complex problems of PAI learning methods which then move the hearts of researchers to try to explore and then examine the questions of the mind mapping method applied by PAI teachers, so that it has the aim of describing the implementation of the mind mapping learning method based on Gitmind software and its implications for students by cultivating an understanding of the subject matter, especially PAI. PTK (classroom action research) is applied to this research action. Data collection applies the method of observation, interviews, documentation and tests. Data reduction, data presentation, data verification are data analysis techniques that apply interactive data analysis methods. This research was conducted in 2 action cycles. The results of the research cycle 1 reached 68% mastery learning and 10% incomplete. Then it increased in cycle 2 by obtaining a mastery learning standard of 93% and 7% which had not been completed. So it was concluded that mind mapping based on Gitmind in Islamic religious education lessons in the learning process was declared successful. Due to the acquisition of test results each cycle increases consistently. The implication of this research is that teachers can take an overview of the application of the Gitmind-based mind mapping method to Islamic religious education lessons to make a new concept of knowledge for the sake of improving and improving science and education in the future.